Influence of the limitation of axillary bud growth on grain and oil yield of castor bean hybrids - Fioreze, Samuel Luiz; Lara-fioreze, Ana Carolina Da Costa; Pivetta, Laerte Gustavo; Rodrigues, João Domingos [UNESP]; Zanotto, Mauricio Dutra [UNESP] (Universidade Federal de Viçosa, 2018)
Cycle reduction and uniform fruit maturation are desired characteristics for a mechanical harvest of castor bean crop. The objective of this research was to study the effect of secondary growth limitation on growth and production parameters of castor bean plants. A field experiment was conducted between February and May 2012 in a randomized block design in a factorial scheme 2 × 2, with four replications. Two castor bean hybrids (Hybrid 12 and Hybrid 18) were grown in two cultivation systems: (i) plants without growth limitation and (ii) plants with secondary stem growth limitation (thinning with pruning). Removal of secondary stems resulted in higher partitioning of assimilates to the primary raceme, promoting higher number and dry weight of grains. As a result, plants with only the primary raceme presented grain yield equivalent to plants without growth limitation. Oil yield of plants with only the primary raceme was equivalent to the control for the Hybrid 12 and higher for the Hybrid 18, with advantage of uniform maturation for these plants.

Redução no ciclo e uniformidade na maturação de frutos são características desejadas para a colheita mecanizada da cultura da mamona. O objetivo do presente trabalho foi estudar o efeito da limitação do crescimento secundário sobre o crescimento e os parâmetros produtivos da mamona. O experimento de campo foi conduzido entre fevereiro e maio de 2012, em delineamento experimental de blocos casualizados e esquema fatorial 2x2, com quatro repetições. Dois híbridos de mamona (Híbrido 12 e Híbrido 18) foram cultivados em duas formas de condução: (i) plantas sem nenhuma limitação ao crescimento e (ii) plantas com limitação do crescimento secundário do caule (poda e desbaste). A limitação do crescimento secundário das plantas resultou em maior partição de assimilados para o racemo primário das plantas, promovendo maior número e massa de grãos. Como resultado, plantas com apenas o racemo primário apresentaram produtividade de grãos equivalente a plantas que cresceram sem limitações. A produtividade de óleo em plantas com apenas o racemo primário foi equivalente a plantas testemunha para o Híbrido 12 e superiores para o Híbrido 18, com a vantagem da obtenção de plantas com maturação uniforme.
Influência da limitação do crescimento de gemas axilares sobre a produtividade de grãos e óleo de híbridos de mamona
Keywords: Ricinus cummunis L; source-sink relationship; plant management; Ricinus cummunis L; fonte-dreno; manejo de plantas